Internet banking usage level of bankers: A research on sampling of Turkey - (:unkn) unknown (IGI Global, 2016)
Banks provide service not only through branches in the countries but also offers banking services to customers over the internet. However, customers concern using internet banking because of the various troubles and adversities that may occur on the web and because of their habits. The using of internet banking is still not reached the desired level due to various reasons such as security, troubles on web and habits of customers. In this research, bankers using rate of internet banking and bankers approach on internet banking are determined. According to the survey results in Turkey, almost all of the bankers use internet banking but using of mobile applications does not appear to fully spread. Even though the using of internet banking is very common among the bankers, some of the participants said that they encountered some problems while using internet banking. Solutions of systemic deficiencies, password security problems and other security problems will increase the using of internet banking. © 2017 by IGI Global. All rights reserved.